2010
DOI: 10.1016/j.jaerosci.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Method for contamination of filtering facepiece respirators by deposition of MS2 viral aerosols

Abstract: 2016-12-24T18:13:07

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 21 publications
0
52
0
Order By: Relevance
“…An added complication is that viruses are often damaged/inactivated during collection using air samplers, due to the stresses and forces acting upon them. 24,[28][29][30][31] To be able to evaluate and compare different methods for detecting viable viral aerosols, our first goal was to develop a system that could safely, efficiently, and consistently generate aerosolized influenza virus. The viral aerosol-generation system was coupled with a bioaerosol sampler for characterizing airborne particles associated with viable influenza viruses.…”
Section: Introductionmentioning
confidence: 99%
“…An added complication is that viruses are often damaged/inactivated during collection using air samplers, due to the stresses and forces acting upon them. 24,[28][29][30][31] To be able to evaluate and compare different methods for detecting viable viral aerosols, our first goal was to develop a system that could safely, efficiently, and consistently generate aerosolized influenza virus. The viral aerosol-generation system was coupled with a bioaerosol sampler for characterizing airborne particles associated with viable influenza viruses.…”
Section: Introductionmentioning
confidence: 99%
“…The plots show that MS2 generally had higher relative recovery and survival at lower RH or AH. In previous studies, MS2 aerosol generally had the highest survival at <30% RH, the lowest survival near 60% RH, and medium survival at >60% RH (Dubovi and Akers 1970;Trouwborst and de Jong 1973;Woo et al 2010). In Appert et al (2012), MS2 was found to have the highest relative recovery at 50% compared with results at 15% and 85% using the same suspension as used in current study.…”
Section: Temperature and Humidity Testsmentioning
confidence: 79%
“…MS2 is a small (25 to 30 nm), non-enveloped, single-stranded RNA (ssRNA) coliphage. It has been frequently tested as a general surrogate for animal and human viruses due to its innocuousness, high stock titer, and rapid analysis (Woo et al 2010;Appert et al 2012). The high stock titer of MS2 compared to AIV and HAdV-1 used in this study gives MS2 an advantage for better virus detection and lower measurement uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Mucin-viscous glycoproteins comprising approximately 75% carbohydrate and 25% amino acids linked via glycosidic bonds between Nacetylgalactosamine and serine or threonine residues-readily forms a gel in water. Details of AS composition were reported by Woo et al (2010).…”
Section: Effects Of Relative Humidity and Spraying Medium On Uv Deconmentioning
confidence: 99%